Intraoral topical anaesthesia in pediatric dentistry: review - SUNNY PRIYATHAM,; SIVAKUMAR NUVVULA, (International Journal of Pharma and Bio Sciences, 2016)
Topical or surface anaesthesia is an important prerequisite for many pediatric dental procedures. Pediatric dentist/dentist should give serious thought to the type of topical and local anaesthesia administered before, during, and after the procedure. Depending on invasiveness of the dental procedure, it is imperative that the clinician choose the best anaesthesia for the job at hand. Clinician should be well versed with type, duration, quantity of topical anaesthesia to be administered in achieving maximum efficiency, without the risk of toxicity. The aim of this review is to provide an insight about topical anaesthetics and their application in various intraoral operative procedures with a special focus on applications in pediatric dentistry, including specific clinical recommendations.